Morvan syndrome: An interesting case of a rare disease (Indian Journal of Case Reports, 2020)
Morvan syndrome is a rare disorder of peripheral nerve hyperexcitability, autonomic and central nervous system hyperactivity. It is considered autoimmune and paraneoplastic in nature. The most common associated antibodies are voltage-gated potassium channel (VGKC) complex antibodies which target leucine-rich glioma inactivated 1(LGI-1) and contactin-associated protein 2 (CASPR-2). It is characterized by myokymia, burning pain, cramps, stiffness, weakness, hyperhidrosis, weight loss, insomnia, and hallucinations. Thymectomy, long-term immunosuppression, plasmapheresis, intravenous immunoglobulin (IVIG), steroids are the treatment options. Carbamazepine, phenytoin, amitriptyline, and benzodiazepine are useful in relieving symptoms. We report a rare case of this disease from western Rajasthan who presented with bilateral diffuse burning pain, cramps, insomnia, weight loss, hyperhidrosis, visual hallucinations, and continuous muscle twitching and rippling activity over the lower back paraspinal muscles. His serum VGKC antibodies were positive. He was treated with IV methylprednisolone (MPS) and IVIG and had a good response to therapy. We should look for rippling muscle movement in a high index of suspicion and should not be missed.